Bismuth tungstate-tourmaline-charcoal adsorption type photocatalyst as well as preparation method and application thereof

Through the preparation method of adsorption photocatalysts of bismuth tungstate-propagation-biochar, combined with the reduction action of ethylene glycol, tourmaline interface electric field and biochar porous structure, the problem of photocatalysts having both adsorption and photocatalytic capabilities is solved, and the photocatalysts are realized. Significantly improve the effect of light response and adsorption performance.

CN119386852AInactive Publication Date: 2025-02-07XI'AN POLYTECHNIC UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510012926.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing photocatalysts are difficult to have excellent adsorption and photocatalytic capabilities, and cannot effectively remove pollutants.

Method used

Using the adsorption photocatalyst preparation method of bismuth tungstate-to-propagation-biochar, oxygen holes are generated through ethylene glycol reduction, combined with the interfacial electric field of tourmaline and the porous structure of biochar, to improve photoresponse and carrier separation with migration capability and adsorption performance.

Benefits of technology

The photoresponse ability, carrier separation and migration efficiency and adsorption performance of the photocatalyst are significantly improved, and the problem of photocatalysts having both adsorption and photocatalytic capabilities is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386852A_ABST
    Figure CN119386852A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth tungstate-tourmaline-charcoal adsorption type photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of wastewater treatment material preparation. The preparation method disclosed by the invention comprises the following steps: S1, adding bismuth salt and tungstate into ethylene glycol, and stirring to obtain a mixed solution; s2, adding tourmaline into the mixed solution, and stirring to obtain a suspension; transferring the suspension into a reaction container A for reaction, and performing post-treatment on the obtained reaction product to obtain the bismuth tungstate-tourmaline composite material. S3, adding the bismuth tungstate-tourmaline composite material and charcoal into deionized water, and stirring to obtain a suspension; and transferring the suspension into a reaction container B for reaction, and performing post-treatment on the obtained reaction product to obtain the bismuth tungstate-tourmaline-charcoal adsorption type photocatalyst. The technical problem that an existing photocatalyst is difficult to have excellent adsorption and photocatalysis capabilities at the same time is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment material preparation, and specifically relates to a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst and a preparation method and application thereof. Background Art

[0002] With the rapid growth of the global economy and population, water pollution has become an increasingly severe challenge. Therefore, the degradation of pollutants in sewage has attracted great attention from researchers. A variety of treatment methods have been explored, including flocculation sedimentation, adsorption, and biological methods. Although these methods have shown certain effectiveness, they also have limitations. The flocculation sedimentation method is less effective in treating specific pollutants and produces a large amount of sludge, resulting in high treatment costs. The adsorption method is limited by the saturation capacity and regeneration difficulties of the adsorbent, and some pollutants are not suitable for removal by adsorption. The biological method may be affected by environmental factors such as temperature and pH, resulting in a slow treatment rate. In contrast, photocatalytic technology directly oxidizes and degrades pollutants by generating photoinduced electrons and holes, showing high degradation efficiency. Photocatalysts can optimize their performance through surface modification and carrier design, so that they can work in the visible light range, thereby expanding their application range. This makes photocatalytic technology show greater potential and advantages in comparison with traditional methods.

[0003] Due to the hybridization of Bi 6s and O 2p orbitals at the valence band maximum, many bismuth-based materials have narrow band gaps, which makes them suitable as visible light responsive photocatalysts. Among them, Bi2WO6 belongs to the Aurivillius phase family and has attracted widespread attention due to its unique layered structure, good visible light catalytic activity, high thermal stability, photochemical stability and environmental friendliness [Chemical Engineering Journal, 2019, 358, 480-496]. Bi2WO6 has been used to remove various pollutants in water pollution control. However, single Bi2WO6 has some limitations as a photocatalyst, such as rapid recombination of photogenerated electrons and holes and poor photocatalytic activity. To address these problems, researchers have proposed several modification strategies, including element doping, metal deposition and heterojunction structure [Molecules, 2023, 28, 8011]. Element doping and metal deposition can change the band structure, thereby improving the photoresponse and redox ability. At the same time, the heterojunction structure can improve the carrier migration rate. However, the photocatalytic efficiency is jointly affected by the light absorption, carrier separation and migration, and redox ability of the photocatalyst. Therefore, how to improve these properties at the same time remains a huge challenge [Chem Catalysis, 2022, 2, 1315–1345]. In addition, the photocatalytic reaction mainly occurs on the surface of the photocatalyst. Photocatalysts with larger pore structures can enrich pollutants and improve their mass transfer diffusion coefficients. However, most of the current photocatalysts have insufficient pore structures, resulting in poor adsorption capacity. Therefore, the preparation of photocatalysts with both excellent adsorption and photocatalytic abilities has become an urgent problem to be solved [Chemical Engineering Journal, 2023, 472, 144893]. Summary of the invention

[0004] The purpose of the present invention is to provide a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst and its preparation method and application, so as to solve the technical problem that the existing photocatalysts are difficult to have both excellent adsorption and photocatalytic capabilities.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst, comprising the following steps: S1: adding bismuth salt and tungstate into ethylene glycol and stirring to obtain a mixed solution; S2: adding tourmaline to the mixed solution, stirring to obtain a suspension; transferring the suspension into a reaction vessel A for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; S3: adding bismuth tungstate-tourmaline composite material and biochar into deionized water, stirring to obtain a suspension; transferring the suspension into reaction vessel B for reaction, and post-treating the obtained reaction product to obtain bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

[0006] Furthermore, in S1, the ratio of the bismuth salt, tungstate and ethylene glycol is 1 mol: (2-2.2) mol: (80-100) mL; the stirring is carried out at room temperature for 30-50 min; The bismuth salt is Bi(NO3)3⋅5H2O; the tungstate is Na2WO4⋅2H2O.

[0007] Furthermore, in S2, before the tourmaline is added to the mixed solution, the tourmaline is ground at room temperature for 30 to 40 minutes; the stirring is carried out at room temperature for 30 to 40 minutes; and after the stirring, ultrasonic treatment is also included, and the ultrasonic treatment time is 20 to 30 minutes, the temperature is 15 to 25°C, and the frequency is 300 to 500kHz.

[0008] Furthermore, in S2, the dosage ratio of the tourmaline to the mixed solution is (0.2-0.4) g: (80-100) mL.

[0009] Further, in S2, the reaction vessel A is a reactor A; the suspension is transferred into the reactor A and placed in a normal pressure drying oven for reaction; the reaction temperature is 120° C. and the reaction time is 24 to 26 hours; The post-treatment includes washing and drying treatments performed in sequence; the washing is performed using ethanol and water for 3 to 5 times respectively; the temperature of the drying treatment is 100 to 120° C. and the time is 120 to 180 minutes.

[0010] Furthermore, in S3, the usage ratio of the bismuth tungstate-tourmaline composite material, biochar and deionized water is (0.1~0.2) g: (0.2~0.3) g: (60~80) mL.

[0011] Furthermore, in S3, the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 30 to 40 minutes before being added to deionized water; the stirring is carried out at room temperature for 30 to 40 minutes; and ultrasonic treatment is also included after the stirring, and the ultrasonic treatment time is 30 to 40 minutes, the temperature is 15 to 25°C, and the frequency is 400 to 600kHz.

[0012] Further, in S3, the reaction vessel B is a reactor B; the suspension is transferred into the reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140° C. and the reaction time is 24 to 26 hours; The post-treatment includes washing and drying treatments performed in sequence; the washing is performed 3 to 5 times with deionized water; the temperature of the drying treatment is 100 to 120° C. and the time is 120 to 180 minutes.

[0013] The invention also discloses a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared by the preparation method.

[0014] The invention also discloses the application of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst in photocatalytic pollutant degradation.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst. Due to the reducing effect of ethylene glycol, the synthesized bismuth tungstate carries a large number of oxygen vacancies, thereby constructing a built-in electric field in the bismuth tungstate; tourmaline has a metal-like property, so the obtained bismuth tungstate-tourmaline composite material can form a good interface electric field on the interface; finally, under the support of the porous characteristics of biochar, the obtained bismuth tungstate-tourmaline-biochar adsorption type photocatalyst not only increases the light response ability, promotes the separation and migration of photogenerated electrons and holes, but also has good adsorption performance, which significantly solves the technical problem that the existing photocatalyst is difficult to have both excellent adsorption and photocatalytic abilities.

[0016] Furthermore, the preparation method disclosed in the present invention only uses the steps of grinding, stirring, reacting in a reactor, cleaning and drying, and has a simple preparation process, low raw material cost, and is suitable for large-scale production.

[0017] Furthermore, the dosage ratio of bismuth salt, tungstate and ethylene glycol is 1 mol: (2-2.2) mol: (80-100) mL, which helps to optimize the reaction conditions and improve the formation efficiency of bismuth tungstate; by stirring at room temperature for 30-40 min, the reaction can be ensured to be uniform, the mixing degree of the reactants can be effectively improved, and the subsequent reaction can be promoted, thereby improving the quality of the final product.

[0018] Furthermore, grinding of tourmaline before mixing can refine the tourmaline particles, allowing them to be better dispersed in the mixed solution, effectively increasing their surface area and reaction activity, promoting their interaction with other components, and thereby enhancing the composite effect of bismuth tungstate and tourmaline.

[0019] Furthermore, the optimal dosage ratio of tourmaline to the mixed solution is provided as (0.2~0.4) g: (80~100) mL, which ensures that the raw materials are fully utilized during the reaction, maintains good reactivity and catalytic activity, reduces material waste, and thus improves economic benefits.

[0020] Furthermore, the reaction temperature is 120°C and the reaction time is 24-26 hours, which can ensure the formation quality of the bismuth tungstate-tourmaline composite material; the cleaning and drying process can remove unreacted substances and impurities, thereby improving the purity and catalytic performance of the final catalyst.

[0021] Furthermore, the dosage ratio of bismuth tungstate-tourmaline composite material, biochar and deionized water is (0.1~0.2) g: (0.2~0.3) g: (60~80) mL, which can ensure sufficient reaction and enhance the adsorption capacity and catalytic efficiency of the final bismuth tungstate-tourmaline-biochar adsorption photocatalyst, thereby improving the treatment effect of photocatalytic pollutant degradation.

[0022] Furthermore, by grinding and ultrasonic treatment of bismuth tungstate-tourmaline composites and biochar, the dispersibility in deionized water was improved and the interaction between the two substances was promoted.

[0023] Furthermore, the reaction temperature is 140°C and the reaction time is 24 to 26 hours, which can ensure the stability and catalytic performance of the final product; the washing and drying treatment settings ensure the removal of impurities and unreacted substances, thereby improving the photocatalytic activity and durability of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

[0024] The present invention also discloses a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared by the above-mentioned preparation method. Due to the synergistic effect between bismuth tungstate, tourmaline and biochar, the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has the advantages of excellent photocatalytic performance and strong adsorption energy, and has excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Figure 2 This is a transmission electron microscopy image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Figure 3 This is a high-resolution transmission electron microscopy image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Figure 4 This is an element distribution diagram of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Among them: (a) -C element; (b) -Bi element; (c) -W element; (d) -O element; (e) -Ca element; Figure 5 This is an X-ray powder diffraction pattern of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Figure 6 This is an XPS (X-ray photoelectron spectroscopy) graph of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention; Among them: a) -XPS total spectrum; b) -XPS fine spectrum of Bi; c) -XPS fine spectrum of W; d) -XPS fine spectrum of O; e) -XPS fine spectrum of C; Figure 7 The N2 adsorption-desorption and pore size distribution diagram of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention and other comparative materials; Figure 8 The UV-visible absorption spectra of N2 of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention and other comparative materials; Fig. 9 The degradation results of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 1 of the present invention and other comparative materials; Fig.10 The degradation results of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 2 of the present invention and other comparative materials; Fig.11 The degradation results of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention and other comparative materials; Fig.12 The degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 1 of the present invention; Fig.13 The degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 2 of the present invention; Fig.14 This is the degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0028] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions).

[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0030] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0031] The present invention provides a method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst, comprising the following steps: S1: adding bismuth salt and tungstate into ethylene glycol and stirring to obtain a mixed solution; S2: adding tourmaline ground at room temperature to the mixed solution, stirring and ultrasonically treating to obtain a suspension; transferring the suspension into a reaction vessel A for reaction, and post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; S3: adding bismuth tungstate-tourmaline composite material and biochar into deionized water, stirring to obtain a suspension; transferring the suspension into reaction vessel B for reaction, and post-treating the obtained reaction product to obtain bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

[0032] Preferably, in S1, the dosage ratio of bismuth salt, tungstate and ethylene glycol is 1 mol: (2-2.2) mol: (80-100) mL; stirring is performed at room temperature for 30-50 min; the bismuth salt is Bi(NO3)3⋅5H2O; and the tungstate is Na2WO4⋅2H2O.

[0033] Preferably, in S2, the tourmaline is ground at room temperature for 30 to 40 minutes; the stirring is stirred at room temperature for 30 to 40 minutes; the ultrasonic treatment time is 20 to 30 minutes, the temperature is 15 to 25°C, and the frequency is 300 to 500kHz; the amount ratio of tourmaline to the mixed solution is (0.2 to 0.4) g: (80 to 100) mL; the reaction container A is a reactor A; the suspension is transferred into the reactor A and placed in a normal pressure drying oven for reaction; the reaction temperature is 120°C and the reaction time is 24 to 26 hours; the post-treatment includes washing and drying treatments performed in sequence; the washing is performed using ethanol and water for 3 to 5 times each; the drying treatment temperature is 100 to 120°C and the time is 120 to 180 minutes.

[0034] Preferably, in S3, the dosage ratio of bismuth tungstate-tourmaline composite material, biochar and deionized water is (0.1~0.2) g: (0.2~0.3) g: (60~80) mL; the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 30~40 min before being added to deionized water; the stirring is stirring at room temperature for 30~40 min; the stirring also includes ultrasonic treatment, the ultrasonic treatment time is 30~40 min, the temperature is 15~25°C, and the frequency is 400~600kHz; the reaction container B is a reactor B; the suspension is transferred to the reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140°C and the time is 24~26h; the post-treatment includes washing and drying treatment performed in sequence; the washing is washing with deionized water for 3~5 times; the temperature of the drying treatment is 100~120°C and the time is 120~180min.

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercially available products, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0037] Example 1 A method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst comprises the following steps: S1: Add Bi(NO3)3⋅5H2O and Na2WO4⋅2H2O into ethylene glycol and stir to obtain a mixed solution; wherein the molar ratio of Bi(NO3)3⋅5H2O to Na2WO4⋅2H2O is 1 mol:2 mol; the amount of ethylene glycol added is 80 mL; the stirring is carried out at room temperature for 30 min; S2: adding tourmaline to the mixed solution, stirring and ultrasonically treating to obtain a suspension; transferring the suspension into reactor A and placing it in a normal pressure drying oven for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; wherein, before the tourmaline is added to the mixed solution, the tourmaline is ground at room temperature for 30 minutes; stirring is performed at room temperature for 30 minutes; the ultrasonic treatment time is 20 minutes, the temperature is 15°C, and the frequency is 300kHz; the amount ratio of tourmaline to the mixed solution is 0.2g:80mL; the reaction temperature is 120°C, and the reaction time is 24h; the post-treatment includes washing and drying treatments performed in sequence; the washing is performed by washing with ethanol and water 3 times each; the drying temperature is 100°C, and the time is 120min; S3: Add bismuth tungstate-tourmaline composite material and biochar to deionized water and obtain a suspension after stirring; after transferring the suspension into reaction vessel B for reaction, post-treating the obtained reaction product to obtain bismuth tungstate-tourmaline-biochar adsorption type photocatalyst; wherein, the amount of bismuth tungstate-tourmaline composite material added is 0.1g; the amount of biochar added is 0.2g, and the amount of deionized water used is 60mL; the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 30min before being added to deionized water; the stirring is stirring at room temperature for 30min; after the stirring, ultrasonic treatment is also included, and the ultrasonic treatment time is 30min, the temperature is 15°C, and the frequency is 400kHz; the reaction vessel B is reactor B; the suspension is transferred to reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140°C and the time is 24h; the post-treatment includes washing and drying treatments performed in sequence; the washing is washing with deionized water for 3 times; the temperature of the drying treatment is 100°C and the time is 120min.

[0038] Example 2 A method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst comprises the following steps: S1: Add Bi(NO3)3⋅5H2O and Na2WO4⋅2H2O into ethylene glycol and stir to obtain a mixed solution; wherein the molar ratio of Bi(NO3)3⋅5H2O to Na2WO4⋅2H2O is 1 mol:2.1 mol; the amount of ethylene glycol added is 90 mL; the stirring is carried out at room temperature for 40 minutes; S2: adding tourmaline to the mixed solution, stirring and ultrasonically treating to obtain a suspension; transferring the suspension into reactor A and placing it in a normal pressure drying oven for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; wherein, before the tourmaline is added to the mixed solution, the tourmaline is ground at room temperature for 35 minutes; stirring is performed at room temperature for 35 minutes; the ultrasonic treatment time is 25 minutes, the temperature is 20°C, and the frequency is 400kHz; the amount ratio of tourmaline to the mixed solution is 0.3g:90mL; the reaction temperature is 120°C, and the reaction time is 25h; the post-treatment includes washing and drying treatments performed in sequence; the washing is performed by washing with ethanol and water 4 times each; the drying temperature is 110°C, and the time is 150min; S3: adding bismuth tungstate-tourmaline composite material and biochar to deionized water, stirring to obtain a suspension; transferring the suspension into reaction vessel B for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst; wherein the amount of bismuth tungstate-tourmaline composite material added is 0.15g; the amount of biochar added is 0.25g, and the amount of deionized water used is 70mL; the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 35min before being added to deionized water; The stirring is carried out at room temperature for 35 minutes; after the stirring, ultrasonic treatment is also included, and the ultrasonic treatment time is 35 minutes, the temperature is 20°C, and the frequency is 500kHz; the reaction container B is a reactor B; the suspension is transferred into the reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140°C and the time is 25 hours; the post-treatment includes washing and drying treatments carried out in sequence; the washing is washed 4 times with deionized water; the temperature of the drying treatment is 110°C and the time is 150 minutes.

[0039] Example 3 A method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst comprises the following steps: S1: Add Bi(NO3)3⋅5H2O and Na2WO4⋅2H2O into ethylene glycol and stir to obtain a mixed solution; wherein the molar ratio of Bi(NO3)3⋅5H2O and Na2WO4⋅2H2O is 1 mol:2.2 mol; the amount of ethylene glycol added is 100 mL; the stirring is carried out at room temperature for 50 minutes; S2: adding tourmaline to the mixed solution, stirring and ultrasonically treating to obtain a suspension; transferring the suspension into reactor A and placing it in a normal pressure drying oven for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; wherein, before the tourmaline is added to the mixed solution, the tourmaline is ground at room temperature for 40 minutes; stirring is performed at room temperature for 40 minutes; the ultrasonic treatment time is 30 minutes, the temperature is 25°C, and the frequency is 500kHz; the amount ratio of tourmaline to the mixed solution is 0.4g:100mL; the reaction temperature is 120°C, and the reaction time is 26h; the post-treatment includes washing and drying treatments performed in sequence; the washing is performed by washing with ethanol and water for 5 times each; the drying temperature is 120°C, and the time is 180min; S3: Add bismuth tungstate-tourmaline composite material and biochar to deionized water, and obtain a suspension after stirring; after transferring the suspension into reaction vessel B for reaction, post-treat the obtained reaction product to obtain bismuth tungstate-tourmaline-biochar adsorption type photocatalyst; wherein, the amount of bismuth tungstate-tourmaline composite material added is 0.2g; the amount of biochar added is 0.3g, and the amount of deionized water used is 80mL; the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 40min before being added to deionized water; the stirring is stirring at room temperature for 40min; after the stirring, ultrasonic treatment is also included, and the ultrasonic treatment time is 40min, the temperature is 25°C, and the frequency is 600kHz; the reaction vessel B is reactor B; the suspension is transferred to reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140°C and the time is 26h; the post-treatment includes washing and drying treatments performed in sequence; the washing is washing with deionized water for 5 times; the drying temperature is 120°C and the time is 180min.

[0040] Figure 1 This is a scanning electron microscope image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. It can be seen that the prepared bismuth tungstate-tourmaline-biochar adsorption type photocatalyst presents a layered stacking morphology.

[0041] Figure 2 This is the transmission electron microscope image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. It can be seen that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst contains both bismuth tungstate and tourmaline as well as biochar. It can be preliminarily concluded that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has been synthesized.

[0042] Figure 3This is a transmission electron microscope image of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. From the image, it can be seen that the characteristic lattice fringes of bismuth tungstate, tourmaline and biochar are clearly visible, which further illustrates the successful synthesis of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

[0043] Figure 4 This is an element distribution diagram of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. It can be seen from the figure that the C, Bi, W, O and Ca elements that constitute the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst are evenly distributed on the surface of the material, that is, the composition of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is uniform; wherein the Ca element is a constituent element of the tourmaline component.

[0044] Figure 5 This is the X-ray powder diffraction pattern of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. It can be seen from the figure that both the characteristic peaks of bismuth tungstate and the characteristic peaks of tourmaline appear in the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst, indicating the successful preparation of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst; since biochar is an amorphous material with no characteristic diffraction peaks, the PXRD (powder X-ray diffraction) measurement was not performed on the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

[0045] Figure 6 This is an XPS graph of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) prepared in Example 3 of the present invention, Figure 6 a) It can be seen that in addition to the characteristic peaks of all elements in bismuth tungstate, there are also peaks of Ca in tourmaline and C in biochar; Figure 6 b)~ Figure 6 e) It can be seen that the detailed XPS spectra of each component element in the composite are shown, indicating that the composite is indeed composed of three components: bismuth tungstate-tourmaline-biochar.

[0046] Figure 7The adsorption-desorption and pore size distribution diagram of N2 of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention is shown. As can be seen from the figure, compared with pure bismuth tungstate, pure biochar and bismuth tungstate-tourmaline (equivalent to the bismuth tungstate-tourmaline composite material prepared in Example 3), the adsorption of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) belongs to the type III mode, indicating that its structure has the characteristics of a mesoporous structure; due to the existence of an H1-type hysteresis loop in the isotherm, it is shown that the pore size distribution of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is relatively uniform; from the pore size distribution diagram, it can be seen that the average pore size of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is approximately between 20 and 40 nm, indicating that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has good adsorption performance due to the addition of biochar.

[0047] Figure 8 This is the UV-visible absorption spectrum of N2 of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) prepared in Example 3 of the present invention. It can be seen from the figure that compared with pure biochar, pure tourmaline and bismuth tungstate-tourmaline (equivalent to the bismuth tungstate-tourmaline composite material prepared in Example 3), the introduction of visible biochar and tourmaline enhances the light response of bismuth tungstate, especially 300~550nm.

[0048] The bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared by the present invention was tested for its photocatalytic pollutant degradation performance. The test followed the national standard in the field of photocatalysis. The specific national standard is as follows: GB / T23762-2009 (Test method for purification of aqueous solution system of photocatalytic material). The data obtained are as follows Figure 9~Figure 11 shown.

[0049] Fig. 9 The degradation result of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) prepared in Example 1 of the present invention, as can be seen from the figure, compared with pure bismuth tungstate, the photocatalytic performance of bismuth tungstate-tourmaline (equivalent to the bismuth tungstate-tourmaline composite material prepared in Example 1) is much improved, and the adsorption performance is also improved; and compared with bismuth tungstate-tourmaline, the adsorption performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is much improved, and the photocatalytic performance is also improved; therefore, the performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is not a simple superposition of adsorption and photocatalytic performance, but the result of the synergistic effect of adsorption and photocatalysis.

[0050] Fig.10The degradation result of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) prepared in Example 2 of the present invention, as can be seen from the figure, compared with pure bismuth tungstate, the photocatalytic performance of bismuth tungstate-tourmaline (equivalent to the bismuth tungstate-tourmaline composite material prepared in Example 2) is indeed much improved, and the adsorption performance is also improved; and compared with bismuth tungstate-tourmaline, the adsorption performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is much improved, and the photocatalytic performance is also improved; therefore, the performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst is not a simple superposition of adsorption and photocatalytic performance, but the result of the synergistic effect of adsorption and photocatalysis.

[0051] Fig.11 The degradation result of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption photocatalyst (represented as bismuth tungstate-tourmaline-biochar in the figure) prepared in Example 3 of the present invention, it can be seen from the figure that compared with pure bismuth tungstate, the photocatalytic performance of bismuth tungstate-tourmaline (equivalent to the bismuth tungstate-tourmaline composite material prepared in Example 3) is indeed much improved, and the adsorption performance is also improved; and compared with bismuth tungstate-tourmaline, the adsorption performance of the bismuth tungstate-tourmaline-biochar adsorption photocatalyst is much improved, and the photocatalytic performance is also improved; therefore, the performance of the bismuth tungstate-tourmaline-biochar adsorption photocatalyst is not a simple superposition of adsorption and photocatalytic performance, but the result of the synergistic effect of adsorption and photocatalysis.

[0052] Fig.12 This is the degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 1 of the present invention. It can be seen from the figure that the tetracycline degradation performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst can still maintain nearly 90% of the performance after five cycles, indicating that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has good stability.

[0053] Fig.13 This is the degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 2 of the present invention. It can be seen from the figure that the tetracycline degradation performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst can still maintain 90% of the performance after five cycles, indicating that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has good stability.

[0054] Fig.14 This is the degradation cycle of tetracycline by the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst prepared in Example 3 of the present invention. It can be seen from the figure that the tetracycline degradation performance of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst can still maintain more than 90% of the performance after five cycles, indicating that the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst has good stability.

[0055] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst, characterized in that: The following steps are involved: S1: adding bismuth salt and tungstate into ethylene glycol and stirring to obtain a mixed solution; S2: adding tourmaline to the mixed solution, stirring to obtain a suspension; transferring the suspension into a reaction vessel A for reaction, and then post-treating the obtained reaction product to obtain a bismuth tungstate-tourmaline composite material; S3: adding bismuth tungstate-tourmaline composite material and biochar into deionized water, stirring to obtain a suspension; transferring the suspension into reaction vessel B for reaction, and post-treating the obtained reaction product to obtain bismuth tungstate-tourmaline-biochar adsorption type photocatalyst.

2. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S1, the dosage ratio of the bismuth salt, tungstate and ethylene glycol is 1 mol: (2-2.2) mol: (80-100) mL; the stirring is carried out at room temperature for 30-50 min; The bismuth salt is Bi(NO3)3⋅5H2O; the tungstate is Na2WO4⋅2H2O.

3. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S2, before the tourmaline is added to the mixed solution, the tourmaline is ground at room temperature for 30 to 40 minutes; the stirring is carried out at room temperature for 30 to 40 minutes; after the stirring, ultrasonic treatment is also included, and the ultrasonic treatment time is 20 to 30 minutes, the temperature is 15 to 25°C, and the frequency is 300 to 500kHz.

4. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S2, the dosage ratio of the tourmaline to the mixed solution is (0.2-0.4) g: (80-100) mL.

5. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S2, the reaction vessel A is a reactor A; the suspension is transferred into the reactor A and placed in a normal pressure drying oven for reaction; the reaction temperature is 120° C. and the reaction time is 24 to 26 hours; The post-treatment includes washing and drying treatments performed in sequence; the washing is performed using ethanol and water for 3 to 5 times respectively; the temperature of the drying treatment is 100 to 120° C. and the time is 120 to 180 minutes.

6. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S3, the dosage ratio of the bismuth tungstate-tourmaline composite material, biochar and deionized water is (0.1~0.2) g: (0.2~0.3) g: (60~80) mL.

7. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S3, the bismuth tungstate-tourmaline composite material and biochar are ground at room temperature for 30 to 40 minutes before being added to deionized water; the stirring is stirred at room temperature for 30 to 40 minutes; and ultrasonic treatment is also included after the stirring, and the ultrasonic treatment time is 30 to 40 minutes, the temperature is 15 to 25°C, and the frequency is 400 to 600kHz.

8. The method for preparing a bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 1, characterized in that: In S3, the reaction vessel B is a reactor B; the suspension is transferred into the reactor B and placed in a normal pressure drying oven for reaction; the reaction temperature is 140° C. and the reaction time is 24 to 26 hours; The post-treatment includes washing and drying treatments performed in sequence; the washing is performed 3 to 5 times with deionized water; the temperature of the drying treatment is 100 to 120° C. and the time is 120 to 180 minutes.

9. A bismuth tungstate-tourmaline-biochar adsorption type photocatalyst, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the bismuth tungstate-tourmaline-biochar adsorption type photocatalyst according to claim 9 in photocatalytic degradation of pollutants.

Citation Information

Patent Citations

  • Hydrangea flower-cluster-shaped bismuth tungstate / biocarbon composite photocatalytic material, preparation method and application thereof

    CN107349927A

  • Preparation method of corn straw biochar-Bi2WO6 photocatalyst for efficiently degrading organic pollutants

    CN111036273A

  • Method for restoring soil polluted by fluoroquinolone antibiotics

    CN115368911A

  • Biochar-modified bismuth vanadate catalyst and preparation method and use thereof

    US20210331149A1